ALGORITHM FOR THE DIAGNOSIS AND TREATMENT OF DISCIRCULATORY ENCEPHALOPATHY IN PATIENTS WITH ARTERIAL HYPERTENSION (Academia Science Repository, 2023)
In clinical practice, both overdiagnosis and underdiagnosis of DE are often observed. To make a correct diagnosis, it is necessary, along with obtaining detailed medical history data, a thorough examination of the neurological status and the state of internal organs (primarily the state of the cardiovascular system), to conduct a number of paraclinical research methods, among which the leading ones are neuroimaging, neuropsychological methods and methods of studying blood vessels supplying the brain.